Patient involvement in improving the evidence base on mental health inpatient care: the PERCEIVE programme - Til Wykes; Emese Csipke; Diana Rose; Thomas Craig; Paul McCrone; Paul Williams; Leonardo Koeser; Stephen Nash (NIHR Journals Library, 2018)
Background: Despite the movement towards care in the community, 40% of the NHS budget on mental health care is still attributed to inpatient services. However, long before the Francis Report highlighted grave shortcomings in inpatient care, there were reports by service user groups on the poor quality of these services in mental health. The programme provides a particular focus on the inclusion of the patient's perspective in the development and evaluation of evidence. Objectives: To understand how changes to inpatient care affect the perceptions of the ward by service users and staff by using stakeholder participatory methods. Design: The programme consisted of four work packages (WPs). (1) Lasting Improvements for Acute Inpatient SEttings (LIAISE): using participatory methods we developed two new scales [Views On Therapeutic Environment (VOTE) for staff and Views On Inpatient CarE (VOICE) for service users]. (2) Client Services Receipt Inventory - Inpatient (CITRINE): working with nurses and service users we developed a health economic measure of the amount of contact service users have with staff. The self-report measure records interactions with staff as well as the number of therapeutic activities attended. (3) Delivering Opportunities for Recovery (DOORWAYS): a stepped-wedge randomised controlled trial to test if training ward nurses to deliver therapeutic group activities would improve the perception of the ward by service users and staff. A total of 16 wards were progressively randomised and we compared the VOICE, VOTE and CITRINE measures before and after the intervention. A total of 1108 service users and 539 staff participated in this trial. (4) Bringing Emergency TreatmenT to Early Resolution (BETTER PATHWAYS) was an observational study comparing two service systems. The first was a 'triage' system in which service users were admitted to the triage ward and then either transferred to their locality wards or discharged back into the community within 7 days. The second system was routine care. We collected data from 454 service users and 284 nurses on their perceptions of the wards. Main outcome measures: The main outcomes for the DOORWAYS and BETTER project were service user and staff perceptions of the ward (VOICE and VOTE, respectively) and the health economic measure was CITRINE. All were developed in WPs 1 and 2. Results: We developed reliable and valid measures of (1) the perceptions of inpatient care from the perspectives of service users and nurses (VOICE and VOTE) and (2) costs of interactions that were valued by service users (CITRINE). In the DOORWAYS project, after adjusting for legal status, we found weak evidence for benefit (standardised effect of -0.18, 95% CI 0.38 improvement to 0.01 deterioration; p = 0.062). There was only a significant benefit for involuntary patients following the staff training (N582, standardised effect of -0.35, 95% CI -0.57 to -0.12; p = 0.002; interaction p-value 0.006). VOTE scores did not change over time (standardised effect size of 0.04, 95% CI -0.09 to 0.18; p = 0.54). We found no evidence of an improvement in cost-effectiveness (estimated effect of £33, 95% CI -£91 to £146; p = 0.602), but resource allocation did change towards patient-perceived meaningful contacts by an average of £12 (95% CI -£76 to £98; p = 0·774). There were no significant differences between the triage and routine models of admission in terms of better perceptions by service users (estimated effect 0.77-point improvement in VOICE score on the triage ward; p = 0.68) or nurses (estimated effect of 1.68-point deterioration in VOTE on the triage ward; p = 0.38) or in terms of the cost of the length of care provided (£391 higher on triage; p = 0.77). Strengths and limitations: We have developed measures using methods involving both service users and staff from mental health services. The measures were developed specifically for acute inpatient services and, therefore, cannot be assumed to be useful for other services. For instance, extensions of the measures are under construction for use in mother and baby units. The strength of the BETTER PATHWAYS and DOORWAYS projects is the large-scale data collection. However, we were testing specific services based in inner city areas and stretching to inner urban areas. It may be that different effects would be found in more rural communities or in different types of inpatient care. Future work: Our database will be used to develop an understanding of the mediating and moderating factors for improving care quality. Trial registration: Current Controlled Trials ISRCTN06545047. Funding: This project was funded by the NIHR Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 6, No. 7. See the NIHR Journals Library website for further project information.